STATISTICAL APPROACH TO FORMING AN ECONOMIC MODEL OF HUMAN POTENTIAL MANAGEMENT IN TOURISM INDUSTRY OF MYKOLAIV REGION - Borysova-Yaryha, Alina M. (Journal of Strategic Economic Research, 2025)
The study aimed to develop an economic model for managing human potential in the tourism sector of Mykolaiv region based on a statistical approach. The creation of a model that took into account socio-economic and demographic factors was based on quantitative and qualitative methods, including contextual analysis, cost-benefit analysis, and benchmarking. It was found that the tourism sector of Mykolaiv region suffered from the significant losses due to the full-scale invasion, caused by its proximity to the combat zone, population outflow, economic downturn, and the inability to conduct strategic planning. Cost-benefit analysis confirmed the feasibility of further development and human potential management for the restoration and sustainable growth of the region’s tourism segment. The proposed economic model for human potential analysis and management included quantitative and qualitative indicators measured using matrices such as professional training assessment; alignment of personal qualities with formal job descriptions; determination of an employee’s work utility; evaluation of work behaviour; level of goal achievement; comprehensive assessment of professional activity; and measurement of employee effectiveness in achieving objectives within a given time frame. Potential challenges in applying the proposed model were considered, including a shortage of qualified personnel and low motivation to work in a sector experiencing a recession. The proposed employee retention and motivation strategies help overcome obstacles to the development of the tourism segment in Mykolaiv region. The research findings can be used to facilitate the post-war recovery of the industry.